2005
DOI: 10.4314/njps.v19i1.32631
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Acuity Loss Of Operators Of Food Grinding Machines In Calabar, Nigeria

Abstract: Summary: Noise has been generally found to cause hearing impairment. This was therefore a comparative study to determine whether chronic exposure to noise generated from food grinding machine can impair hearing acuity. Forty food grinding machine operators in Watt and Marian markets, Calabar, who were exposed to noise for at least 6 months formed the test subjects. Control subjects, however, were age-and sexmatched staff and students of the University of Calabar and University of Calabar Teaching Hospital, Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The standard measurement of noise exposure in relation to health of an individual in an environment should be in the range of 80 to 90 dBA. In a recent study of effects of noise on Nigerian workers, it was reported that 100% of workers which include the petty traders exposed to noise for a period of 14 years, developed hearing impairments (Ighoroje et al, 2004;Bisong et al, 2004). A similar result from a study was reported by Yesufu et al (2013).…”
Section: Introductionsupporting
confidence: 59%
“…The standard measurement of noise exposure in relation to health of an individual in an environment should be in the range of 80 to 90 dBA. In a recent study of effects of noise on Nigerian workers, it was reported that 100% of workers which include the petty traders exposed to noise for a period of 14 years, developed hearing impairments (Ighoroje et al, 2004;Bisong et al, 2004). A similar result from a study was reported by Yesufu et al (2013).…”
Section: Introductionsupporting
confidence: 59%
“…Ozer et al (2009) revealed a very high noise level in some areas of Tokat city, Turkey which includes public structures, hospitals, schools and houses with noise levels over 75 dB, while Osemeikhian and Anomohanran (2006) recorded noise levels above 90 dBA in Warri, Nigeria. High noise levels may predispose residents of this study area to health problems such as noise-induced hearing loss, tinnitus, insomnia and headache, as reported by Bisong et al (2004) that members of the community that are exposed to 105.8±9.24 dBA of noise level suffered from noise-induced hearing loss, tinnitus, insomnia and headache. There is a special concern for the children attending the various schools located very close to the industrial area as it could be a serious source of distraction among other effects.…”
Section: Resultsmentioning
confidence: 64%
“…In Calabar-Nigeria, operators of food grinding machines suffered health effects like hearing loss and symptoms such as tinnitus, insomnia and headache. Operators were exposed to noise for at least six (6) months at 105.8 dB [40]. Furthermore, researchers in Tanzania found out that the power plant section of a cement factory produced noise level of 104.8 dBA which exceeded the allowed limit value of 85 dBA as recommended by Tanzania Bureau of Standards (TBS).…”
Section: Industriesmentioning
confidence: 99%